Male Nursing Students’ Perception of Gender Barriers in Nursing Curricula in an Iranian University of Medical Sciences - Hosseini, Fahimeh Alsadat; Parvan, Kobra; Shaygan, Maryam; Thomson, Brian (Investigación y Educación en Enfermería, 2023)
Objective. The present study aimed to determine male nursing students’ perception of gender barriers in nursing curricula. Methods. This descriptive study was conducted on 150 B.Sc. and M.Sc. nursing students at Tabriz School of Nursing and Midwifery, Tabriz university of medical sciences, Tabriz, Iran that were selected through convenience sampling. The study data were collected using Inventory of Male Friendliness in Nursing Programs-Short (IMFNP-S). This scale has 17 items for investigating male nursing students’ perception of gender barriers in nursing curricula. Each item is a 5-point Likert-type scale scored from 0 to 4; total scale score could range from 0 to 68, higher scores representing male nursing students’ perception of less gender barriers in nursing curricula. Results. The total mean score of gender barriers was 35.11+6.15. The most important barriers included different requirements/limitations in obstetrics apprenticeship (Median=1), and need for proving oneself because of people’s expectation of nurses to be female (Median=2). On the other hand, the least important barriers were lack of important people’s support on one’s career decisions (Median=3), and lack of opportunity to work with other male nurses (Median=3). The scale score was not associated with the socio-demographic characteristics studied. Conclusion. The most male nursing students feel various gender issues in the nursing curriculum in a medium level that may negatively impact on their learning, professional performance and motivation and tendency to nursing. Furthermore, this vicious cycle can lead to lack of professional development, leaving the job and burnout. Thus, creating a gender-neutral environment can make nursing programs more male friendly.